Thianthrene-functionalized polynorbornenes as high-voltage materials for organic cathode-based dual-ion batteries. Issue 83 (3rd August 2015) - Speer, Martin E.; Kolek, Martin; Jassoy, Jean Jacques; Heine, Jennifer; Winter, Martin; Bieker, Peter M.; Esser, Birgit
Abstract : Thianthrene polynorbornenes are investigated as high-voltage organic cathode materials for dual-ion cells with a charge/discharge potential of 4.1 V vs. Li/Li + . Abstract : Thianthrene-functionalized polynorbornenes were investigated as high-voltage organic cathode materials for dual-ion cells. The polymers show reversible oxidation reactions in solution and as a solid in composite electrodes. Constant current investigations displayed a capacity of up to 66 mA h g −1 at a high potential of 4.1 V vs. Li/Li + .